Peran Komunikasi Digital Dalam Pelayanan Pengelolaan Arsip Aktif Di Dinas Kearsipan Provinsi Sumatera Selatan (Studi Pada Penerapan Seikandi) - Meri Septiani; M Fajar Riando (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study aims to analyze the role of digital communication in supporting the effectiveness of active archive management services at the South Sumatra Provincial Archives Office, particularly through the implementation of the SRIKANDI application. In the era of digitalization, communication faces challenges in managing complex information. The government encourages the development of electronic government (SPBE) in accordance with Presidential Regulation Number 95 of 2018. SRIKANDI is an innovation to manage digital archives systematically, integratively, and according to ANRI standards. This study uses a descriptive qualitative method, with primary data sourced from interviews with archivists and secondary data from related documents. The research results indicate that digital communication through SRIKANDI plays an important role in improving service effectiveness through faster information delivery, information accuracy, ease of access, certainty of service flow, and process transparency. However, this success is influenced by factors such as human resource (HR) readiness and the need for habituation and in-depth understanding of the system to achieve consistent optimal use.